Guidelines for a palliative approach for aged care in the community setting: A suite of resources - Toye, Christine; Blackwell, S.; Maher, S.; Currow, D.; Holloway, K.; Tieman, J.; Hegarty, M. (2012)
In Australia, many people ageing in their own homes are becoming increasingly frail and unwell, approaching the end of life. A palliative approach, which adheres to palliative care principles, is often appropriate. These principles provide a framework for proactive and holistic care in which quality of life and of dying is prioritised, as is support for families. A palliative approach can be delivered by the general practitioner working with the community aged care team, in collaboration with family carers. Support from specialist palliative care services is available if necessary.The Guidelines for a Palliative Approach for Aged Care in the Community Setting were published by the Australian Government Department of Health and Ageing to inform practice in this area. There are three resource documents. The main document provides practical evidence based guidelines, good practice points, tools, and links to resources. This document is written for general practitioners, nurses, social workers, therapists, pastoral care workers, and other health professionals and responded to needs identified during national consultation. Evidence based guidelines were underpinned by systematic reviews of the research literature. Good practice points were developed from literature reviews and expert opinion. Two 'plain English' booklets were developed in a process involving consumer consultation; one is for older people and their families, the other for care workers.The resources are intended to facilitate home care that acknowledges and plans for the client's deteriorating functional trajectory and inevitable death. At a time when hospitals and residential aged care facilities are under enormous pressure as the population ages, such a planned approach makes sense for the health system as a whole. The approach also makes sense for older people who wish to die in their own homes. Family needs are recognised and addressed. Unnecessary hospitalisations or residential placements and clinically futile interventions are also minimised.